Associação entre nível de expressão de microRNAs e aspectos histopatológicos de displasia em leucoplasia bucal - Joao Artur Ricieri Brito (2013)
Increased expression of microRNAs (miRNAs), miR-21, miR-345, and miR-181b, has been demonstrated in oral leukoplakia (OL) that progresses to oral squamous cell carcinoma (OSCC), suggesting a miRNA signature with potential prognostic value. On the basis of these findings, this pilot study aimed to investigate the cytological and histopathological features that are used to grade oral dysplasia and determine associations with the expression of these 3 potentially cancer-related miRNAs. We also compared the expression levels of these miRNAs in OL with normal oral mucosa and OSCC. We evaluated miRNA expression by qPCR in 22 samples of OL demonstrating different grades of dysplasia, as well as 17 cases of OSCC, and 6 samples of normal oral mucosa. We associated the miRNAs expression profiles with cytological and histopathological features of OL. OSCC cases showed increased expression of all 3 miRNAs when compared with OL and normal oral mucosa. Increased expression of miR-21 was also observed in OL when compared with normal oral mucosa. We found a higher expression of miR-21 and miR-181b in OL that presented with an increased number of mitotic figures, increased nuclear-cytoplasmic ratio, or hyperchromasia. Increased expression of miR-21 was also detected in OL with abnormally superficial mitosis. Higher expression of miR-345 was observed in OL with an increased number and size of nucleoli or increased nuclear-cytoplasmic ratio. In conclusion, the present study shows that some cytological and histopathological parameters used to grade dysplasia are associated with altered miRNA expression.